USING VIDEO SUBTITLES TO IMPROVE STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXTS - Supangesti, Pitria; Sutapa, Gatot; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to improve reading comprehension in narrative texts to the ninth grader at SMPN 1 Singkawang. The researcher applied four strategies taken from Westwood: carefully viewing and overviewing what to be read, self questioning, selectively reading and summarizing. These strategies were implemented through three sequences; pre-viewing, while viewing and post viewing. The study showed that the use of video subtitles gave positive implication which effected on learning improvement. A set of sequences in video subtitles assisted the students in understanding the text, interpreting words, and improve their vocabularies. The students’ attitude towards their reading comprehension have improved, which was shown engaged actively during the learning process and their responses towards the strategy used. Moreover, the students also improved their score. Thus, it indicated that the learning process have run well and have increased individual performance. Keywords: Video Subtitles, Reading Comprehension, and Narrative Texts.